Museums in cultural tourism in Poland - Krakowiak, Beata (Turyzm/Tourism, 2013)
The article presents the museums, their potential and their significance for cultural tourism in Poland. Its aims are achieved through a presentation of registered national museums, ‘monuments of history’, museum buildings and the cultural activities undertaken by these institutions.